Peningkatan Efektivitas Kerja Staf Administrasi Melalui Penerapan Analisis Pekerjaan (Studi Kasus Pada Kantor Notaris Ebony Kiki Haga, S.H., M.Kn. Di Kota Balikpapan) - Ririn Kusumawati; Mada Aditya Wardana; Azahra Nur Akhirina (Lembaga Pengembangan Kinerja Dosen, 2023)
A notary is a public official who aims to serve the public in the field of legal services in making authentic deeds by the Law of the Republic of Indonesia Number 30 of 2004. This goal can be achieved if human resource management provides job descriptions and specifications to achieve employee work effectiveness one of which is the Notary Office of Ebony Kiki Haga, S.H., M.Kn, which requires employee work effectiveness in service activities. In this case, the administrative staff is the most important role related to the effectiveness of the notary's office. Work effectiveness has not been achieved properly because there is no defined job description and specifications, so there is often a miscommunication regarding the division of work. This research method uses descriptive qualitative. Data collection techniques using field methods (observation), interview methods, and documentation methods. The data analysis technique uses qualitative analysis, namely by reducing data, presenting data, and drawing conclusions, then testing the credibility of the data using the triangulation method. The result of this research is that the work effectiveness of administrative staff has met 3 (three) indicators of work effectiveness, after doing job analysis with the results being able to apply job descriptions and specifications for administrative staff.